Surface water quality in high and low flow seasons in the Middle Awash River, Ethiopia, 2022 - Kebede, E; Zinabu, E (University of Oxford, 2024)
In a study to investigate temporal and spatial dynamics of irrigation water quality in the Middle Awash River, samples were taken at 10 sites along the river. Water quality parameters measured include physical characteristics (PH, Turbidity, TDS, Temperature, suspended solids and Dissolved solids, DO), chemical characteristics (dissolved cations (Ca, Mg, Na and K), alkalinity (HCO3- and CO32-), Cl-, NO3-) and Heavy metals (Boron, Arsenic, Copper, Chromium, Lead, Zinc, Manganese, Mercury and Nickel). Please see the readme file for more detailed notes on study location and methodology.